2016
DOI: 10.1055/s-0035-1570397
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Pollicis Longus Rupture after Mini TightRope Suspensionplasty

Abstract: Symptomatic degenerative joint disease of the first carpometacarpal (CMC) joint has been successfully managed with various surgical treatments including trapeziectomy alone, trapeziectomy and ligament reconstruction with or without tendon interposition, metacarpal osteotomy, CMC arthrodesis, and CMC prosthetic arthroplasty; currently, no single approach has shown superiority. Clinical Relevance The aim of this case report was to cite an occurrence of EPL rupture following its use and discuss the possibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…11 Other complications with the use of the suture-button suspension have been described, including fracture of the index metacarpal and rupture of the extensor pollicis longus tendon; however, these complications were typically noted with earlier generations of the implant and were not encountered in the present study. 25,26 The primary limitation of this study is its retrospective, single academic center nature. The operations were exclusively performed by the 2 senior authors (B.T.E.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other complications with the use of the suture-button suspension have been described, including fracture of the index metacarpal and rupture of the extensor pollicis longus tendon; however, these complications were typically noted with earlier generations of the implant and were not encountered in the present study. 25,26 The primary limitation of this study is its retrospective, single academic center nature. The operations were exclusively performed by the 2 senior authors (B.T.E.…”
Section: Discussionmentioning
confidence: 99%
“…Early treatment of symptomatic thumb CMC OA was to remove the trapezium and allowing the metacarpal to essentially float into the void created. Long-term results of simple trapeziectomy demonstrate excellent pain relief and maintenance of metacarpal range of motion but with significant proximal migration of the thumb CMC joint 3,34,35. This loss in height decreases the lever force of the metacarpal, resulting in a significant decrease in postoperative pinch strength 34.…”
Section: Late-stage Pantrapezial Arthritismentioning
confidence: 99%
“…Park et al demonstrated that LRTI arthroplasty utilizing a segment of the FCR tendon autograft had longer operative times on average and lower preservation of strength at the final follow-up when compared to hematoma distraction arthroplasty and costochondral allograft interposition arthroplasty with ligament reconstruction (Figure 6G). 24 Owing to reports of complications such as complex regional pain syndrome following the traditional trapeziectomy with LRTI arthroplasty, several alternative techniques have been described to provide similar stability and metacarpal height maintained by this procedure 5,20,2935Trapeziectomy with joint replacement and ligament reconstruction: the use of an implant helps to prevent proximal subsidence of the metacarpal, especially when combined with ligament reconstruction using the TightRope implant to reconstruct the volar oblique ligament connecting the thumb to the index metacarpal (Figure 6H).…”
Section: Late-stage Pantrapezial Arthritismentioning
confidence: 99%
“…Potential complications of this approach have been reported: index metacarpal fractures, tissue reaction leading to osteolysis, extensor pollicis longus tendon rupture, suspensionplasty collapse with subluxation of the thumb metacarpal and pain, overtightening of the suture button with resulting symptomatic impingement of the first and second metacarpal bases, and discomfort from superficially located hardware. 5,[13][14][15][16] Our purpose is to evaluate our results with trapeziectomy and suspensionplasty with a suture button in the treatment of thumb basilar arthritis, with a minimum of 18 months of follow-up. Our primary outcomes were first ray subsidence into the trapezial space and rate of complications.…”
Section: Introductionmentioning
confidence: 99%
“…Potential complications of this approach have been reported: index metacarpal fractures, tissue reaction leading to osteolysis, extensor pollicis longus tendon rupture, suspensionplasty collapse with subluxation of the thumb metacarpal and pain, overtightening of the suture button with resulting symptomatic impingement of the first and second metacarpal bases, and discomfort from superficially located hardware. 5 13 14 15 16…”
Section: Introductionmentioning
confidence: 99%